Effects of concept mapping strategy on sentence construction, paragraphing and editing in junior secondary schools students’ composition writing achievements - Gowon, Rahila P.; Yashim, Haddy Y. (Frontiers in Education, 2022)
This study investigated the effects of concept mapping on sentence construction, paragraphing, and editing in composition writing achievement of secondary school students in Kafanchan Education Zone, Kaduna State Nigeria. The study answered three research questions and tested three hypotheses. Quasi-experimental (non-equivalent pre-test-post-test control group design) research design was employed for the study. The population of the study included all the 1,242 Junior Secondary School two (JS II) students in 35 public secondary schools in Kafanchan Education Zone of Kaduna State. Sample of 66 students from two intact classes (experimental group = 36, control group = 30) participated in the study. Students in the experimental group received 8-weeks of training on concept mapping instruction, while those in the control group were exposed to normal conventional teaching. Students’ Composition Writing Achievement Test (SCWAT, test-retest reliability = 0.78) was developed by the researcher to obtain baseline information and after-intervention information. Data were analysed using descriptive statistics (means & standard deviation) and analysis of covariance (ANCOVA). Results indicated that students have the very low ability in sentence construction, paragraphing, and editing in composition writing achievement at baseline. Also, concept mapping instruction significantly improved students’ ability to construct a cohesive sentence, develop a paragraph, and edit composition writing. The study concluded that concept mapping strategy has significant effects on sentence construction, paragraphing, and editing in composition writing achievement skills of junior secondary school students. The study strongly recommended the use of a concept mapping strategy by teachers, students, and school administrators in Nigeria.